When Defense Technologies Meet Human Experience: Evaluating the UX of F-16 Strikes, BM-21 Rockets, and White Phosphorus in the Thailand–Cambodia Conflict - Alya, Syariefa; Jandhana, I.B Putra; Basworo, Gregorius Henu (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines civilian experiences during the 2025 Thailand–Cambodia border conflict using a User Experience (UX) approach. Through diary studies and the experience sampling method (ESM), supported by an adapted HEART framework, the research shows that F-16 strikes created anticipatory fear, BM-21 rockets disrupted essential daily activities, and white phosphorus caused long-term trauma and reduced trust in state institutions. The findings highlight that military technology assessment must consider humanitarian impacts and civilian experiences rather than focusing solely on tactical effectiveness.